Decision making in contexts of deep uncertainty - An alternative approach for long-term climate policy. Issue 103 (January 2020) - Workman, Mark; Dooley, Kate; Lomax, Guy; Maltby, James; Darch, Geoff
Highlights: There is a strong tendency to view IAMs as providing objective analysis. Largescale reliance of IAM scenarios on CDR is problematic for a number of reasons. Dependence on CDR is being baked into emissions targets without a public debate. Polarisation on CDR could hinder progress on CDR and alternative strategies. Approaches to allow diversity in value-sets in climate policy making is essential. Abstract: The majority of global emissions scenarios compatible with holding global warming to less than 2 °C depend on the large-scale use of bioenergy with carbon capture and storage (BECCS) to compensate for an overshoot of atmospheric CO2 budgets. Recent critiques have highlighted the ethical and environmental risks of this strategy and the danger of building long-term climate policy on such speculative technological scenarios emerging from integrated assessment models. Here, we critically examine both the use of BECCS in mitigation scenarios and the decision making philosophy underlying the use of integrated assessment modelling to inform climate policy. We identify a number of features of integrated assessment models that favour selection of BECCS over alternative strategies. However, we argue that the deeper issue lies in the tendency to view model outputs as objective science, capable of defining "optimal" goals and strategies for which climate policy should strive, rather than as exploratory tools within a broader policy development process. This model-centric decision making philosophy is highly sensitive to uncertainties in model assumptions and future trends, and tends to favour solutions that perform well within the model framework at the expense of a wider mix of strategies and values. Drawing on the principles of Robust Decision Making, we articulate the need for an alternative approach that explicitly embraces uncertainty, multiple values and diversity among stakeholders and viewpoints, and in which modelling exists in an iterative exchange with policy development rather than separate from it. Such an approach would provide more relevant and robust information to near-term policymaking, and enable an inclusive societal dialogue about the appropriate role for carbon dioxide removal within climate policy.